Control of contextual memory through interneuronal α5-GABAA receptors. Issue 4 (11th April 2023) - Zhu, Mengwen; Abdulzahir, Alifayaz; Perkins, Mark G; Chu, Chan C; Krause, Bryan M; Casey, Cameron; Lennertz, Richard; Ruhl, David; Hentschke, Harald; Nagarajan, Rajasekar; Chapman, Edwin R; Rudolph, Uwe; et al.
Abstract: γ-Aminobutyric acid type A receptors that incorporate α5 subunits (α5-GABAA Rs) are highly enriched in the hippocampus and are strongly implicated in control of learning and memory. Receptors located on pyramidal neuron dendrites have long been considered responsible, but here we report that mice in which α5-GABAA Rs have been eliminated from pyramidal neurons (α5-pyr-KO) continue to form strong spatial engrams and that they remain as sensitive as their pseudo-wild-type (p-WT) littermates to etomidate-induced suppression of place cells and spatial engrams. By contrast, mice with selective knockout in interneurons (α5-i-KO) no longer exhibit etomidate-induced suppression of place cells. In addition, the strength of spatial engrams is lower in α5-i-KO mice than p-WT littermates under control conditions. Consistent with the established role of the hippocampus in contextual fear conditioning, α5-i-KO mice resisted etomidate's suppression of freezing to context, but so too did α5-pyr-KO mice, supporting a role for extra-hippocampal regions in the development of contextual fear memory. Overall, our results indicate that interneuronal α5-GABAA Rs serve a physiological role in promoting spatial learning and that they mediate suppression of hippocampus-dependent contextual memory by etomidate.